2022
DOI: 10.15252/emmm.202115326
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 vaccine induces antibody release in saliva: a possible role for mucosal viral protection?

Abstract: Vaccination against an airborne pathogen is very effective if it induces also the development of mucosal antibodies that can protect against infection. The mRNA‐based vaccine‐encoding SARS‐CoV‐2 full‐length spike protein (BNT162b2, Pfizer/BioNTech) protects also against infection despite being administered systemically. Here, we show that upon vaccination, cognate IgG molecules are also found in the saliva and are more abundant in SARS‐CoV‐2 previously exposed subjects, paralleling the development of plasma Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 37 publications
8
43
0
Order By: Relevance
“…Systemic immunization with poliovirus or rubella virus induces corresponding antibodies in the circulation but not in secretions, whereas oral or intra-nasal immunization achieves the converse: antibodies, mostly of the IgA isotype, induced in intestinal, salivary, and nasopharyngeal secretions ( 11 ). The systemic Pfizer mRNA vaccine has been reported to induce weak IgA responses in saliva and nasal secretions especially in previously infected subjects ( 20 , 34 36 ), interestingly with a predominance of the IgA1 subclass ( 37 ) which is susceptible to cleavage by bacterial IgA1 proteases ( 38 ). Unfortunately, there are no available data to compare these findings with mucosally delivered SARS-CoV-2 vaccines to determine if results similar to those obtained with polio or rubella vaccines are valid also for SARS-CoV-2, although there is no reason to think otherwise.…”
Section: Separate and Independent: Mucosal And Systemic Immunitymentioning
confidence: 99%
“…Systemic immunization with poliovirus or rubella virus induces corresponding antibodies in the circulation but not in secretions, whereas oral or intra-nasal immunization achieves the converse: antibodies, mostly of the IgA isotype, induced in intestinal, salivary, and nasopharyngeal secretions ( 11 ). The systemic Pfizer mRNA vaccine has been reported to induce weak IgA responses in saliva and nasal secretions especially in previously infected subjects ( 20 , 34 36 ), interestingly with a predominance of the IgA1 subclass ( 37 ) which is susceptible to cleavage by bacterial IgA1 proteases ( 38 ). Unfortunately, there are no available data to compare these findings with mucosally delivered SARS-CoV-2 vaccines to determine if results similar to those obtained with polio or rubella vaccines are valid also for SARS-CoV-2, although there is no reason to think otherwise.…”
Section: Separate and Independent: Mucosal And Systemic Immunitymentioning
confidence: 99%
“…Nevertheless, our data show that vaccination with 3 doses has an impact on disease duration, that might be due also to an increased mucosal IgA and/or IgG content in a subgroup of responders and not only to cellular response ( 56 ). In this way, development of new vaccines able to induce a stronger IgA response might hopefully strengthen the protection ( 57 ).…”
Section: Discussionmentioning
confidence: 71%
“…It has indeed been suggested that the lack of anti-SARS-Cov-2 IgA and secretory IgA might explain COVID-19 severity, vaccine failure, prolonged viral shedding and reinfection ( 55 ). On the other hand, higher SARS-CoV-2 specific IgG than IgA levels have been reported in the saliva of immune-competent vaccinated patients, and IgG salivary concentration increases in parallel with the increase of specific serum IgG levels ( 56 ). We might thus hypothesize that mabs administration may lead to a rapid increase of SARS-CoV-2 specific antibodies in saliva, thus justifying the beneficial effect of mabs also in patients with limited spontaneous IgA production.…”
Section: Discussionmentioning
confidence: 99%
“…Of the included articles, 11 are longitudinal studies ( 12 , 16 , 25 28 , 30 , 32 , 35 37 ), and four are cross-sectional studies ( 29 , 31 , 33 , 34 ). All studies were published in English between 2021 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published in English between 2021 and 2022. Five of them were conducted in Italy ( 25 , 27 , 28 , 31 , 32 ), three in United States ( 12 , 16 , 33 ), three in Germany ( 30 , 34 , 35 ), two in Canada ( 26 , 36 ), one in Croatia ( 29 ), and one in Australia ( 37 ).…”
Section: Resultsmentioning
confidence: 99%